Conductivity, dielectric relaxation and structural studies of PEO complexed with lithium acetate and lithium triflate salts - Ismail, L.; Teo, L.P.; Arof, Abdul Kariem (2009)
Polyethylene oxide (PEO) films doped with lithium acetate (LiOAc) and lithium triBI (LiOTf) were prepared by the solution cast technique. Lithium acetate was added to PEO different weight ratios ranging from 0 wt. % to 30 wt. % whereas lithium triB' concentration was varied from 0 wt. % to 14 wt. %. The polymer-salt solutions were cast into different glass containers and left to dry until the films have formed. The samples were then characterized by electrical impedance spectroscopy (EIS) to obtain the electrical conductivity and to determine the dielectric properties of both systems. The highest room temperature electrical conductivity obtained for PEO-LiOAc system is 2.18 x 10-6 S cm-1 for the sample containing 30 wt. % lithium acetate and 8.22 x 10-6 Scm-I for PEO-LiOTf system at 12 wt·. concentration of lithium triflate. From the Argand plots, it was found that the relaxation process in PEO-LiOAc system is attributed to the viscoelastic relaxation and for PEO-LiO system, it is due to conductivity relaxation.